Delayed manifestation of Isolated Intramural Hematoma of the duodenum resulting from Blunt abdominal Trauma - Tae Sun Ha; Jun Chul Chung (Journal of Trauma and Injury)
Duodenal injury following blunt abdominal trauma is a relatively unusual complication, and it may sometimes be difficult to distinguish a duodenal hematoma from duodenal perforation. According to recent reports, intramural hematomas typically resolve spontaneously with conservative treatment. Surgery, however, is occasionally necessary in some cases if the diagnosis is delayed, conservative therapy fails, or a high degree of suspicion of duodenal injury persists. We experienced a case of delayed manifestation of a duodenal intramural hematoma that was surgically treated.